Identification at Biovar Level of Brucella Isolates Causing Abortion in Small Ruminants of Iran. (27th November 2012) - Behroozikhah, Ali Mohammad; Bagheri Nejad, Ramin; Amiri, Karim; Bahonar, Ali Reza
Abstract : To determine the most prevalent biovar responsible for brucellosis in sheep and goat populations of Iran, a cross-sectional study was carried out over 2 years in six provinces selected based on geography and disease prevalence. Specimens obtained from referred aborted sheep and goat fetuses were cultured on Brucella selective media for microbiological isolation. Brucellae were isolated from 265 fetuses and examined for biovar identification using standard microbiological methods. Results showed that 246 isolates (92.8%) were B. melitensis biovar 1, 18 isolates (6.8%) were B. melitensis biovar 2, and, interestingly, one isolate (0.4%) obtained from Mazandaran province was B. abortus biovar 3. In this study, B. melitensis biovar 3 was isolated in none of the selected provinces, and all isolates from 3 provinces (i.e., Chehar-mahal Bakhtiari, Markazi, and Ilam) were identified only as B. melitensis biovar 1. In conclusion, we found that B. melitensis biovar 1 remains the most prevalent cause of small ruminant brucellosis in various provinces of Iran.